Nozzle flow dynamics during control system response of pulse width modulated (PWM) technology-equipped agricultural sprayer - Fabula, Jonathan Viernes (Kansas State University, 2021)
Crop producers utilize agricultural sprayers equipped with modern technologies such as pulse width modulation (PWM) system that can manage flow at nozzle-by-nozzle, thus have the potential to provide greater resolution for section control and reducing the environmental contamination. The introduction of precision technologies such as the PWM system has obvious benefits to the producers; however, a greater understanding of system functionality and operational accuracy is required for adoption and implementation. One of the greatest challenges is to manage nozzle level target application rate for large self-propelled systems during active section control and ground speed transitions. Therefore, this study was conducted to quantify the PWM system's performance under real-world operating conditions, with a goal to develop knowledge for producers to accurately implement this technology and suggest technology improvements for manufacturer's. A methodology was established to conduct system-level evaluation of the PWM system both in laboratory and field settings. In the laboratory setting, the pressure and flow dynamics of three commercially available PWM systems (Capstan PinPoint, John Deere ExactApply, and Raven Hawkeye) were evaluated. On the other hand, field tests were conducted using a New Holland SPF370F and Case Patriot 4440 agricultural sprayer to evaluate the PWM system's performance in varying field conditions. Both sprayers were equipped with a Raven Hawkeye PWM system and had a 36.6 m boom width. Novel analytical techniques were developed to generate a high spatial control-section level mapping of system performance parameters to quantify advantages and instances of application rate errors. Laboratory test results show that different PWM systems provided different pressure drops when applying different application rates and pressures. The pressure drop was unique for different PWM systems, and it significantly increased with the increase in the application rate for three systems. The pressure drop could vary the nozzle flow rate, which may significantly impact the application rate, thereby reducing the product efficacy. A pressure drop greater than 70.0 kPa from the target application pressure could cause the flow rate to vary beyond ±10.0% error. The three PWM systems also had an ON/OFF latency before attaining the target application pressure and inherent fall time before the system stops spraying after the solenoid valves close. These latencies could increase the error, particularly when using a system that operates at a higher frequency. Moreover, the PWM systems operated at stable pressures for less than the specified duty cycle time may have resulted in the inaccurate nozzle flow rate observed during the study. The tests were conducted with a specific nozzle, however, it is very much possible that different nozzles might also exhibit different magnitudes of pressure drop. In the field tests, the PWM system maintained the target application pressure within the acceptable range for 77.0% to 89.0% of the time, indicating its ability to provide the application rate within the ±10.0% error. The pressure CV was below 5.0% for most of the time, signifying a consistent pressure between boom sections during operation. These results were significantly improved from using a flow-based system when applying the product at similar settings wherein it only operates for 32.0% of the time within the ±10.0% error. The droplet size spectra deviation when using a PWM system could occur mainly due to the improper nozzle selection. The system may deliver consistent droplet size spectra if the selected nozzle provides the desired droplet size within the wide range of application pressure thus, providing uniform product application. The systems' ability to manage pressure and thus provide uniform droplet spectra is particularly important for nozzle flow rate management and managing drift potential. Moreover, the duty cycle accuracy within ±5.0% was lower in fields with irregular shapes and varying terrain (12.0%) than in a rectangular field with relatively flat terrain (54.0%). Accurate duty cycle implementation is the key to achieving an accurate application rate; therefore newer approach as implemented during these tests might be executed to quantify control system response enhancements. The application rate accuracy within ±5.0% error was also lower in irregular-shaped fields (10.0% of the time) than the rectangular fields (46.0% of the time). Furthermore, the PWM system varied the duty cycles on the inner and outer boom section based on each control section's ground speed at various turning radii. The turn compensation functionality significantly reduced the application errors on curvilinear passes, thus effectively controlling pests and minimizing pesticide resistance and environmental damage. In conclusion, crop producers will continue to adopt new liquid application technologies such as the PWM system to improve product application efficiency. However, operators should understand the system component and control system responses to achieve desired performance in the varying field and operating conditions to reduce the application errors. Future research and development on nozzle pressure monitoring, flow dynamic optimization during the application cycle, and new sensor integration for accurate duty cycle implementation might be considered to refine real-time nozzle flow management to truly realize the concept of precision agriculture to reduce application error, pesticide resistance, and environmental pollution.
Keywords: Agricultural sprayer; Application pressure uniformity; Application rate error; Control system response time; Pulse width modulation; Turn compensation